Cellular Immune Responses in Islet Xenograft Rejection - Hu, Min; Hawthorne, Wayne J.; Yi, Shounan; O’Connell, Philip J. (Frontiers in Immunology, 2022)
Porcine islets surviving the acute injury caused by humoral rejection and IBMIR will be subjected to cellular xenograft rejection, which is predominately mediated by CD4+ T cells and is characterised by significant infiltration of macrophages and T cells (CD4+ and CD8+). Overall, the response is stronger than allograft rejection and more difficult to suppress. Activation of CD4+T cells is both by direct and indirect antigen presentation. After activation they induce donor specific antibodies and recruit macrophages. Although they are less important than CD4+ T cell-initiated islet xenograft rejection, macrophages are believed to be a major effector cell in this response. Rodent studies have shown that xenoantigen-primed and CD4 T cell-activated macrophages were capable of recognition and rejection of pancreatic islet xenografts, and they destroyed a graft via the secretion of various proinflammatory mediators, including TNF-α, reactive oxygen and nitrogen species, and complement factors. Moreover, as human macrophages expressing SIRP-α are found to be lacking a species-appropriate CD47, a marker of self, this cross-species molecular incompatibility also contributes to macrophage activation and the rejection of porcine xenogeneic target cells. Regulatory T cells are important for moderating the T cell mediated response and will be discussed in detail. Thus strategies that expand their influence and inhibit and/or reduce macrophage activation are required for use in combination with clinical applicable immunosuppressive agents to achieve effective suppression of the T cell-initiated xenograft response.